PERBEDAAN POLA DESAIN EKSPERIMENTASI KAMPANYE GERILYA DENGAN PRODUKSI SENI RUPA PENYADARAN DI INDONESIA - Retno Setyowati Rahardjo, Fransisca (Kartala, 2025)
In recent decades, guerrilla campaigns have colored the advertising world in Indonesia. Although the production of these works is not particularly active, the development of creativity in this medium can be considered significant. Beginning with inspiration from the creative world abroad, activation designers in Jakarta, in particular, have increasingly conducted experiments with the approaches in their works. On the other hand, the contemporary art scene has also developed rapidly. With the advent of internet and digital technologies, which allow vast amounts of information from outside to be transferred in a relatively short period of time, performative and performance art have emerged as part of this growing trend. Performance art has even been considered the precursor that led Indonesian visual arts to move towards a contemporary school of thought through the Black December event by GSRB (Gerakan Seni Rupa Baru) in 1975. Today, works of art and design have developed freely under the name of globalization, making it difficult to distinguish between art and design works. From a philosophical perspective, this may seem redundant to analyze because, in essence, both are part of a single working cycle. However, in the professional realm within different industry mechanisms, the author believes it is important to clarify the issue. Therefore, this research aims to outline the differences in working methods between the contemporary art industry and visual communication design industry in today’s context, based on case studies of viral campaign products in urban cities (Jakarta-Bandung) over the past decade.